Case report: Cholangiocarcinoma and dysgerminoma in white-winged guan (Penelope albipennis), Peru - Vásquez, Gloria (2020)
The case of a 7-year-old white-winged guan (Penelope albipennis) with sudden death, owned by a zoo and rescue center in Lambayeque, Peru, is reported. At necropsy, diffusely scattered whitish spots were observed in the liver and whitish nodules of different sizes in the ovary. Histopathological examination gave the definitive diagnosis of cholangiocarcinoma in the liver and dysgerminoma in the ovary. This is the first report of these pathologies in the Penelope albipennis species in Peru.